Be Wide Awake: Aggressiveness on Children (International Journal of Nursing Education, 2021)
Background of the Study: Aggression is one of the most prevalent behavioral aspects in children whichcause a lot of concern in present days. Reactively aggressive children do not seek to meet goals throughaggressive behavior. Instead they react negatively to perceived or actual threats and are easily irritated.Objective: The study examines the aggressive behavior among school children attending higher primaryschool in selected village, Mangalore.Methods: A non-experimental descriptive design was chosen to assess the aggressive behavior amongchildren by using a Modified Overt Aggression Scale and total of 60 samples were selected using theSnowball sampling technique.Results: The findings clearly revealed that 48 subjects (80%) were having mild aggressive behavior. Withregard to the association of demographic variables, religion, birth order, occupational status of parents,family income and parents opinion regarding aggressive behavior had statistically significant associationwith the aggressive behavior among children attending higher primary school at p
Keywords: Aggressive behavior, Children, Higher primary school, Modified overt aggression scale, Snowball sampling.